Effects of Soil Salinity and Alkalinity on Mohpho-physiological Parameters of Pearl Millet - Gupta, S C; Lal, P; Muralia, R N; Kumar, Arvind; Srivastava, J P (Annals of Arid Zone, 2016)
A pot experiment was conducted in completely randomised design with two levels of salinity (ECe 3.7 and 10. 8 mmhos/cm) and two levels of alkalinity (SAR 14. 5 and 34. 5) in the soil to study their effect on morpho-physiological parameters of pearl millet cv BJ-104 and BK-56J during vegetative phase of growth. There was a general reduction in all the growth parameters under salinity-alkalinity stress. An increase in leaf proline content of BJ-104 was noted. There was no significant effect on mid-day stomatal behaviour of the plants. Both the genotypes were found susceptible to the combined stress due to salinity and alkalinity but exhibited moderate tolerance towards either salinity or alkalinity stress.